Annual reports on NMR spectroscopy. - Webb, G. A. (Graham Alan), 1935- (Annual reports on NMR spectroscopy ;, 1994)
This collection of reports demonstrate the extensive purview of NMR and its applications. The pellucid presentations provided include accounts on application of NMR spectroscopy to sciences and technologies of glassand ceramics; high-resolution solid-state NMR studies on ceramics; NMR studies of zeolite; NMR studies of higher-order structures of solid polymers; and organic thin films. Taken together with reviews in other volumes of this series, the present accountsably demonstrate that NMR is facile princeps when it comes to problem solving in most areas of science, including the medical sciences.